Fixed bed adsorption of diquat dibromide from aqueous solution using carbon nanotubes1. Issue 76 (19th August 2015) - Dichiara, Anthony B.; Harlander, Samuel F.; Rogers, Reginald E.
<x xml:space="preserve">Abstract</x> Carbon nanotubes are increasingly studied as attractive adsorbents for wastewater treatment. The present work exploits the attributes of different types of CNTs in a fixed bed column for the dynamic uptake of diquat dibromide from aqueous solutions.